2017
DOI: 10.1515/geo-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

CRSP, numerical results for an electrical resistivity array to detect underground cavities

Abstract: This paper is devoted to the application of the Combined Resistivity Sounding and Profiling electrode configuration (CRSP) to detect underground cavities. Electrical resistivity surveying is among the most favorite geophysical methods due to its nondestructive and economical properties in a wide range of geosciences. Several types of the electrode arrays are applied to detect different certain objectives. In one hand, the electrode array plays an important role in determination of output resolution and depth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(32 reference statements)
2
6
0
Order By: Relevance
“…In line with our results, the field study and numerical modeling have shown that the DD array can accurately resolve the subsurface structures such as cavity [38,67], thin dike [25], buried wall [29,32], and sinkhole [21]. These structures were moderately recovered by the WS and PD arrays [24,26,69]. The pole-pole array is generally the poorest in terms of model accuracy and image quality [25,32], consistent with our study.…”
Section: Experimental Cavity Studysupporting
confidence: 89%
See 2 more Smart Citations
“…In line with our results, the field study and numerical modeling have shown that the DD array can accurately resolve the subsurface structures such as cavity [38,67], thin dike [25], buried wall [29,32], and sinkhole [21]. These structures were moderately recovered by the WS and PD arrays [24,26,69]. The pole-pole array is generally the poorest in terms of model accuracy and image quality [25,32], consistent with our study.…”
Section: Experimental Cavity Studysupporting
confidence: 89%
“…Compared to the numerical results, the experimental cavity anomaly in all the tested arrays showed considerable underestimation of anomaly depth. The depth underestimation in cavity studies can lead to inappropriate interpretation, similar to other field studies [26,68]. Since our study was conducted in shallow sandy clay, the patchily distributed high and low resistive features were inferred as the inversion artefacts.…”
Section: Experimental Cavity Studysupporting
confidence: 58%
See 1 more Smart Citation
“…Engineering geophysics provides solutions to a wide range of environmental and engineering problems associated with construction (Sharma, 1997; Lei et al ., 2006; Yalcinkaya et al ., 2016). A variety of engineering geophysical methods have been used to detect underground cavities, including resistivity (Kemna et al ., 2002; Fasani et al ., 2013; Zhang et al ., 2014; Amini and Ramazi, 2017), transient electromagnetic methods (Zhang et al ., 2011), ground‐penetrating radar (GPR) (Booth et al ., 2011; Anchuela et al ., 2014) and shallow seismic methods (Grandjean et al ., 2002). However, the volumetric effects of electrical prospecting methods, environmental limitations of GPR and the high cost of cross‐hole geophysics often make these approaches insufficient for meeting the high‐resolution and low‐cost exploration needs of urban underground cavities.…”
Section: Introductionmentioning
confidence: 99%
“…Resistivity methods, especially 2D and 3D electrical resistivity imaging (ERI) techniques are very useful in this situation. Application of these techniques for geotechnical site characterization is very useful to determine the subsurface geology and the subsurface structures such as cavities, voids, soil stability (Auken et al, 2006: Sudha et al, 2009Wisén et al, 2012;Mohammad, 2012;Loke et al, 2013;Thabit and Abed, 2014;Abdelwahab, 2013;Hassan and Nsaif, 2016;Amini and Ramazi, 2017;Hassan et al, 2018 andAziz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%